2004
DOI: 10.1111/j.1467-789x.2004.00149.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric medication‐induced obesity: treatment options

Abstract: A majority of psychiatric medications are known to generate weight gain and ultimately obesity in some patients. The authors undertook a comprehensive literature review in order to provide a better understanding of novel treatment options in regards to alleviating weight gained by use of antidepressants, antipsychotics, and mood stabilizers. There are no agents for management of this weight gain approved by the Food and Drug Administration (FDA), and existing studies on options are mainly uncontrolled, small-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
32
0
3

Year Published

2006
2006
2016
2016

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(35 citation statements)
references
References 48 publications
(46 reference statements)
0
32
0
3
Order By: Relevance
“…47,48 According to recent studies, VAT is highly responsive to exercise and dietary interventions, [49][50][51] and to a variety of pharmaceuticals. 52,53 It is thus increasingly desirable to find effective methods of monitoring changes in VAT in both clinical interventions and epidemiologic studies. The mechanism behind the reduction in abdominal adipose tissue with acupuncture therapy remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…47,48 According to recent studies, VAT is highly responsive to exercise and dietary interventions, [49][50][51] and to a variety of pharmaceuticals. 52,53 It is thus increasingly desirable to find effective methods of monitoring changes in VAT in both clinical interventions and epidemiologic studies. The mechanism behind the reduction in abdominal adipose tissue with acupuncture therapy remains unclear.…”
Section: Discussionmentioning
confidence: 99%
“…Use of adjunctive weight loss agents such as sibutramine, orlistat, or topiramate has not been subject to adequate testing to be broadly recommended. [52][53][54][55] A systematic review of 16 studies testing approaches to limit weight gain associated with antipsychotics found that 5 of 8 pharmacologic intervention studies reported small (<5%) reductions in body weight, whereas those with behavioral interventions also reported small reductions in body weight or weight maintenance. 56…”
Section: Approaches To Limit Undesirable Weight Gain With Psychiatricmentioning
confidence: 97%
“…People were instructed to collect medication containers before filling in this questionnaire. The use of antidepressants, lithium and antipsychotic drugs as psychotropic drugs were included as these drugs influence body weight (Schwartz et al, 2004). Somatic co-morbidity, other than cardiovascular disease or diabetes mellitus was lumped together and coded as present or absent.…”
Section: Potential Confoundersmentioning
confidence: 99%